Analisis ekonomi budidaya Ikan Mas (Cyprinus carpio) KJA waduk PLTA Koto Panjang - Dukut Tri Sadono; Darwis AN; Zulkarnain Umar (Dinamika Lingkungan Indonesia, 2021)
This study aims to analyze the factors that affect income levels, estimate economic value, analyze financial feasibility and study alternative policies for the development of goldfish (Cyprinus carpio) cultivation in floating net cages in an effort to develop fishery potential in Koto Panjang Hydroelectric Reservoir, Kampar Regency, Riau Province. The sampling location is determined based on (purposive sampling). The method used in this research is a survey method. Determination of the population in the study using the Census method. Factors that significantly influence the income of goldfish cultivators (Cyprinus carpio) at the real level α = 5% are the yield (HP) kg / unit and the number of cages (JK) unit. The surplus value of goldfish cultivation producers (Cyprinus carpio) is IDR 42,102,269,258.00 / year. The results of the analysis of the financial feasibility value (NPV) of Rp. 77,136,617.10, - / unit for the volume of cages 6 x 6 x 4. Whereas for the volume of cages 6 x 8 x 4, it has a value (NPV) which is much greater than Rp. . 173,394,632.39, - / unit. The second value (NPV) is positive based on the criteria for a feasible business investment if the value (Net B / C) is greater than 1, the value (IRR) is the same as 12.00% for both cage size categories. The sensitivity analysis shows that the cultivation of goldfish (Cyprinus carpio) KJA in the Koto Panjang Hydroelectric Power Plant is more sensitive to changes in decreased production compared to changes in decreasing price of carp feed (Cyprinus carpio). Based on the Exponential Comparative Analysis (MPE), it is found that the best alternative development policies to be developed and implemented are capital strengthening and improvement of facilities and infrastructure related to fish cultivation development.